2004
DOI: 10.1016/j.neuron.2004.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dscam Diversity in Regulating Axon Guidance in Drosophila Mushroom Bodies

Abstract: Dscam is an immunoglobulin (Ig) superfamily member that regulates axon guidance and targeting in Drosophila. Alternative splicing potentially generates 38,016 isoforms differing in their extracellular Ig and transmembrane domains. We demonstrate that Dscam mediates the sorting of axons in the developing mushroom body (MB). This correlates with the precise spatiotemporal pattern of Dscam protein expression. We demonstrate that MB neurons express different arrays of Dscam isoforms and that single MB neurons expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

24
299
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(326 citation statements)
references
References 60 publications
24
299
3
Order By: Relevance
“…Is this process highly regulated or does it occur in a random or stochastic manner? Microarray experiments have revealed little if any regulation of exon 6 splicing 11,27 , which is consistent with the biology of Dscam. In the nervous system, it seems that the actual identity of the Dscam isoforms that are expressed is unimportant, provided that each neuron expresses a different set of isoforms than the neighboring neurons 11,[28][29][30][31] .…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Is this process highly regulated or does it occur in a random or stochastic manner? Microarray experiments have revealed little if any regulation of exon 6 splicing 11,27 , which is consistent with the biology of Dscam. In the nervous system, it seems that the actual identity of the Dscam isoforms that are expressed is unimportant, provided that each neuron expresses a different set of isoforms than the neighboring neurons 11,[28][29][30][31] .…”
supporting
confidence: 63%
“…Microarray experiments have revealed little if any regulation of exon 6 splicing 11,27 , which is consistent with the biology of Dscam. In the nervous system, it seems that the actual identity of the Dscam isoforms that are expressed is unimportant, provided that each neuron expresses a different set of isoforms than the neighboring neurons 11,[28][29][30][31] . Similarly, within the immune system, where Dscam functions in a manner analogous to vertebrate antibodies 13,16 , hemocytes must be capable of expressing most if not all of the potential Dscam isoforms to mount an effective immune defense against invading pathogens.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…And finally, Dscam1 is required for the segregation of sister branches in mushroom body neurons, a process similar to self-avoidance [8]. These observations led to the proposal that Dscam1 promotes homophilic repulsion in vivo [9] [7]. Note that in previous publications we referred to this Dscam paralog as Dscam.…”
Section: Reviewmentioning
confidence: 83%
“…Expression studies in mushroom body neurons (as well as several other subclasses) argue that many isoforms are expressed in each neuron and that the expression pattern is largely random [6]. In addition, genetic studies demonstrated that the type of isoform expressed in each MB neuron is not important; rather, what is crucial is that an individual MB neuron expresses different isoforms from its neighbors [9][10][11].…”
Section: Reviewmentioning
confidence: 99%